2017
DOI: 10.1007/s00432-017-2434-2
|View full text |Cite|
|
Sign up to set email alerts
|

Homogeneous pancreatic cancer spheroids mimic growth pattern of circulating tumor cell clusters and macrometastases: displaying heterogeneity and crater-like structure on inner layer

Abstract: It is possible to establish 3D CTC cluster models from homogenous PDA cell lines using hanging drop and ultra-low attachment plates. PDA cell line displays its own intrinsic properties or heterogeneity. The mechanism of formation of the crater-like structure as well as golf ball-like structure needs further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Based on these limitations, we considered the forced floating method using ULA plates as the most suitable and straightforward method to generate RT4 spheroids for cytotoxicity assays. Our findings corroborate with the literature reporting promising results using ULA method with different types of tumor cells (Vinci et al, 2012 ; Howes et al, 2014 ; Feng et al, 2017 ; Selby et al, 2017 ).…”
Section: Resultssupporting
confidence: 93%
“…Based on these limitations, we considered the forced floating method using ULA plates as the most suitable and straightforward method to generate RT4 spheroids for cytotoxicity assays. Our findings corroborate with the literature reporting promising results using ULA method with different types of tumor cells (Vinci et al, 2012 ; Howes et al, 2014 ; Feng et al, 2017 ; Selby et al, 2017 ).…”
Section: Resultssupporting
confidence: 93%
“…Such results are consistent with the observation in Ishikawa endometrial cells that a unicellular hollow spheroid is the starting point for differentiation of a multicellular hollow spheroid (Fleming, 2019). Multicellular hollow spheroids may well proliferate inward to form solid spheroids, a process observed for pancreatic spheroids (Feng et al, 2017) but not yet observed in Ishikawa spheroids. What has been observed is that hollow spheroids can proliferate outward by forming additional attached hollow spheroids (Fleming, 2018a).…”
Section: Mitonucleons Are Also Observed In Ishikawa Epithelial Tubulessupporting
confidence: 90%
“…As the gas vacuole within the mitonucleon in a single monolayer cell expands, it pressures polyploid nuclei against the cytoplasmic membrane and the developing spheroid detaches from the monolayer, having been converted from an anchored into a mobile "cell". Researchers studying spheroid formation in pancreatic cancer cell lines (Feng et al 2017), elicited structures capable of growth as various kinds of spheroids by an alternative method called high-throughput single-cell derived sphere formation. The method is like cloning but uses a sophisticated device to guarantee single cell distribution in conditions favoring non-attachment (Chen et al, 2015).…”
Section: Mitonucleons Are Also Observed In Ishikawa Epithelial Tubulesmentioning
confidence: 99%
“…Nevertheless, the similarities between these clumps and CTC clusters (with respect to cell–cell contacts and expression of CTC-specific markers) have not been fully addressed. Likewise, complex methods for the development of multicellular and single cell-derived tumor spheroids from established pancreatic cell lines (using hanging drop and ultra-low attachment plates) have been recently reported as means to mimic the growth pattern of CTC clusters ( 28 ), but the size and morphology of these spheroids (large compact or hollow spheres) have little similarities to isolated CTC clusters.…”
Section: The Problemmentioning
confidence: 99%